Wine and Oil - Kykeion and Istrian Supa - Milićević Bradač, Marina (2007)
Wine is a well known commodity from the prehistoric times and was consumed in many different ways. Equally oil was known for a very long time and was gradually gaining importance in the Mediterranean diet. It is therefore not surprising that the combination of wine and other food - cheese, oil, spices, honey and specially fried corn or bread, was common diet. Famous is the Homeric kykeố n and that particular way of preparing dishes with wine survived until modern times, e.g. in Istria, where the so called Istrian supa is the national specialty.
Projekt MZOS
Projekt MZOS
ENG